Criação de um Vade Mecum educacional da atividade fim ensino dos Institutos Federais - Neves, Luciano Oliveira Azevedo (2019)
Federal Institutes of Education (FIs) have a public character, which means that they are governed by general and specific legislation. Laws are often difficult to understand by education actors, such as teachers, technicians and managers. And with an aggravating factor: they are dispersed, making knowledge and handling even more difficult to support many educational actions and decisions. In this sense, this study aimed to create the Vade Mecum Educacional, which is the compilation and detailing of all national laws regarding teaching activities, with special emphasis on those developed by the FIs. He used the scientific-technological method, which is characterized by the generation of guiding questions, followed by the collection and organization of laws, stages that configure the scientific part of the method; then the laws were modeled around a Vade Mecum prototype, whose functionality and effectiveness were tested with evaluations by professionals from the teaching area of the Federal Institute of Amazonas (IFAM), and recommendations for improvement were made and submitted to a new evaluation. , configuring the tested and approved final product. The final product consists of a chronological index of the legislation on education, a list of abbreviations and acronyms, 49 constitutional provisions, 9 ordinary laws, an IFAM normative resolution, a technical glossary and an alphabetical and remissive index of the legislation. The conclusion shows that the use of the product in the teaching activities of the FIs will provide more technical and legal security both in its planning and execution and in the managerial decision-making process. The contribution of this study to the area of professional and technological education is to guarantee a reliable and updated legal support so that professionals can develop their activities safely and without temerity